2019
DOI: 10.1289/ehp4745
|View full text |Cite
|
Sign up to set email alerts
|

New Toxicology Tools and the Emerging Paradigm Shift in Environmental Health Decision-Making

Abstract: BACKGROUND: Numerous types of rapid toxicity or exposure assays and platforms are providing information relevant to human hazard and exposure identification. They offer the promise of aiding decision-making in a variety of contexts including the regulatory management of chemicals, evaluation of products and environmental media, and emergency response. There is a need to consider both the scientific validity of the new methods and the values applied to a given decision using this new information to ensure that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…While high throughput in vitro assays may be helpful for prioritization, there are many limitations that should be kept in mind ( Ginsberg et al, 2019 ; Krewski et al, 2020 ). For example, the assays typically don’t have metabolic capacity, which can lead to false positive and negative results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While high throughput in vitro assays may be helpful for prioritization, there are many limitations that should be kept in mind ( Ginsberg et al, 2019 ; Krewski et al, 2020 ). For example, the assays typically don’t have metabolic capacity, which can lead to false positive and negative results.…”
Section: Resultsmentioning
confidence: 99%
“…US EPA’s ToxCast chemical screening program has tested many pesticides for these endpoints using high and medium-throughput in vitro assays that use a variety of human cell lines such as MCF-7 breast cancer and H295R adrenocortical carcinoma cells ( Thomas et al, 2019 ). These publicly-available data are an important resource despite the known limitations of in vitro testing such as the lack of metabolic capability of cells tested, influence of chemical properties affecting bioavailability, uncertain relevance of cell lines used in in vitro assays to normal tissue, and uncertainty in extrapolating effects across tissues or even multiple cell types in a single tissue ( Ginsberg et al, 2019 ; Krewski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the need for diverse high-throughput in vitro data streams to rapidly inform hazard identification and to fill the knowledge gap for chemicals with minimum toxicity data, challenges remain about their use in prioritization and screening level assessment strategies as well as tradeoffs between speed and uncertainty ( Paul Friedman et al, 2020 ). For instance, while high throughput screening data could play key roles in decision-making for emergency response, there are many limitations with respect to predicting chemical fate and effects in the environment, challenges that might lead to potentially missed hazards ( Ginsberg et al, 2019 ). Furthermore, there is also uncertainty in the extrapolation from in vitro bioactivity to in vivo toxicity ( Bell et al, 2018 ), and gaps exist in the cell-based in vitro screening and potential effects on human health since most cell assay endpoints are still related to cytotoxicity and non-specific effects ( Judson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples over the last decade include applications to hazard identification of oil dispersant formulations (Judson et al, 2010), environmental samples (Blackwell et al, 2017(Blackwell et al, , 2019Escher et al, 2018;Horzmann et al, 2017;Neale et al, 2020), petroleum substances (Grimm et al, 2016;Kamelia et al, 2019), and botanicals (Catlin et al, 2018). The high-throughput format of in vitro assays allows for rapid testing, and it has been suggested that additions of in vitro bioactivity data to mixture risk assessment may hold promise in reducing uncertainties (Drakvik et al, 2020;Ginsberg et al, 2019). It has also been posited that cell-based bioassays can be used in support of environmental quality standards (Escher et al, 2018).…”
mentioning
confidence: 99%